TRAINING ON MAKING SHORT VIDEOS TO SUPPORT THE PROVISION OF EDUCATION TO TECHNOLOGY-BASED COMMUNITIES - Saputro, Immanuela Puspasari; Sanger, Junaidy Budi; Adrian, Angelia Melani (SEEIJ (Social Economics and Ecology International Journal), 2023)
DAGUSIBU is one of the programs of the Indonesian Pharmacists Association that aims to provide education on how to get, use, store, and dispose of medicines correctly. Before the pandemic, socialization of this program is conducted by gathering the public in a place and health workers providing education directly. However, the Covid-19 pandemic has changed many settings, including how DAGUSIBU education is provided. Instagram is one of the social media that is widely used by Indonesians. It has a feature called reels that allows the owner to upload short videos, and they will not disappear except the owner delete them. But not everyone knows how to make educational reels/stories that are interesting and aesthetic. For this reason, our team intends to provide training on making Instagram reels or stories by utilizing the Canva Application. Based on the results from the pretest and posttest questionnaires given to the participants, it can conclude that the training activities for making Instagram reels using the Canva Application can be well understood and followed by the participants.